2019
DOI: 10.3389/fneur.2019.00073
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation in Spinocerebellar Ataxia: A Pilot Randomized Controlled Trial

Abstract: Spinocerebellar ataxia (SCA) is a neurodegenerative disorder caused by dysfunction of the cerebellum and its connected neural networks. There is currently no cure for SCA and symptomatic treatment remains limited. We aimed here to examine the effects of a repetitive transcranial magnetic stimulation (rTMS) targeting the cerebellum on clinical impression, postural control and gait in patients with SCA. In this randomized, double-blinded and sham-controlled study, 20 individuals aged 18–75 years with SCA confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…This functional change was accompanied by improvement in several objective metrics of postural sway during eyes-open and eyes-closed standing. rTMS did not influence performance in the nine-hole peg test, the timed up-and-go test, or gait kinematics [64].…”
Section: Clinical Studiesmentioning
confidence: 74%
“…This functional change was accompanied by improvement in several objective metrics of postural sway during eyes-open and eyes-closed standing. rTMS did not influence performance in the nine-hole peg test, the timed up-and-go test, or gait kinematics [64].…”
Section: Clinical Studiesmentioning
confidence: 74%
“…56 Finally, Manor and colleagues recently published the outcomes of a randomized, double-blind, sham-controlled trial in which 20 subjects with various genetically confirmed spinocerebellar ataxias (SCAs) received 20 daily sessions of the aforementioned TMS regimen. 57 Unfortunately, there were significant baseline differences between the rTMS and sham groups, with the former exhibiting a lower score on the Scale for the Assessment and Rating of Ataxia (SARA), which denotes less severe ataxia, and a faster execution of the Nine-Hole Peg Test (9HPT). The investigators therefore computed the percent change in each outcome from baseline to follow-up and reported a larger decrease in SARA score after one month in rTMStreated patients, which proved to be due to a better performance on the stance item only.…”
Section: Degenerative Cerebellar Ataxiasmentioning
confidence: 99%
“…Using an identical TMS protocol in a single patient with idiopathic late‐onset cerebellar atrophy, Farzan and colleagues noticed improvements in speech, dysmetria, and tremor, increased gait speed in normal walking and during cognitive dual tasking, and decreased postural sway, paralleled by a reduction of CBI that persisted after six months . Finally, Manor and colleagues recently published the outcomes of a randomized, double‐blind, sham‐controlled trial in which 20 subjects with various genetically confirmed spinocerebellar ataxias (SCAs) received 20 daily sessions of the aforementioned TMS regimen . Unfortunately, there were significant baseline differences between the rTMS and sham groups, with the former exhibiting a lower score on the Scale for the Assessment and Rating of Ataxia (SARA), which denotes less severe ataxia, and a faster execution of the Nine‐Hole Peg Test (9HPT).…”
Section: Effects Of Noninvasive Cerebellar Stimulation In Diseases Afmentioning
confidence: 99%
“…Overall, these studies included patients with cerebellar ataxia due to stroke, 5,[72][73][74] degenerative causes, [75][76][77][78][79][80][81][82][83][84] or cerebral palsy, 85 with a total of 237 patients. Nine studies were double-blind.…”
Section: Effects Of Cerebellar Modulation On Ataxiamentioning
confidence: 99%
“…Nine studies were double-blind. 5,73,74,76,80,[82][83][84][85] Eight studies used TMS stimulation, 5,72,73,[75][76][77]84,86 seven used transcranial direct current stimulation (tDCS), [78][79][80][81][82][83]85 and 1 implanted a DBS device. 74 The time of evaluation after the intervention ranged from immediately after the stimulation to 1 year after the stimulation.…”
Section: Effects Of Cerebellar Modulation On Ataxiamentioning
confidence: 99%